The Kinase USK1 Regulates Cellulase Gene Expression and Secondary Metabolite Biosynthesis in Trichoderma reesei - Beier, Sabrina; Hinterdobler, Wolfgang; Monroy, Alberto Alonso; Bazafkan, Hoda; Schmoll, Monika (Frontiers in Microbiology, 2020)
The complex environment of fungi requires a delicate balance between the efforts to acquire nutrition, to reproduce and to fend off competitors. In Trichoderma reesei, an interrelationship between regulation of enzyme gene expression and secondary metabolism was shown. In this study, we investigated the physiological relevance of the unique YPK1-type kinase USK1 of T. reesei. Usk1 is located in the vicinity of the SOR cluster and is involved in regulation of several genes from this secondary metabolite cluster as well as dihydrotrichotetronine and other secondary metabolites. Moreover, USK1 is required for biosynthesis of normal levels of secondary metabolites in liquid culture. USK1 positively influences cellulase gene regulation, secreted cellulase activity and biomass formation upon growth in constant darkness on cellulose. Positive effects of USK1 on transcript abundance of the regulator of secondary metabolism, vel1 and the carbon catabolite repressor gene cre1 are in agreement with these functions. In summary we found that with USK1, T. reesei comprises a unique kinase, that adds an additional layer of regulation to the connection of secondary metabolism and enzyme production in fungi.